Studi Komparatif: Implementasi Kebijakan Luar Negeri Indonesia Dan Kuwait Terkait Pemberian Humanitarian Aid Terhadap Polemik Palestina – Israel - Alia, Nazwa; Zebua, Kerenhapukh Valentina; Simbolon, Sherly Desinta; M, Natasya Ulkhaira Adhian; Haliawan, Prity Oktora; Noer, Arvenia; Yuningsih, Neneng Yani (UIR Press, 2024)
The Palestinian conflict with Israel has been going on for centuries, beginning in the mid-1800s/ Tensions rose with Jewish migration to Palestine and the 1917 Balfour Declaration in favor of establishing a